Avian species identity drives predation success in tropical cacao agroforestry. Issue 3 (17th March 2015) - Maas, Bea; Tscharntke, Teja; Saleh, Shahabuddin; Dwi Putra, Dadang; Clough, Yann; Siriwardena, Gavin
Summary Avian ecosystem services such as the suppression of pests are considered to be of high ecological and economic importance in a range of ecosystems, especially in tropical agroforestry. However, how bird predation success is related to the diversity and composition of the bird community, as well as local and landscape factors, is poorly understood. We quantified arthropod predation in relation to the identity and diversity of insectivorous birds using experimental exposure of artificial, caterpillar‐like prey in 15 smallholder cacao agroforestry systems differing in local shade‐tree management and distance to primary forest. The bird community was assessed using both mist‐netting (targeting active understorey insectivores) and point counts (higher completeness of species inventories). Bird predation was not related to local shade‐tree management or overall bird species diversity, but to the activity of insectivorous bird species and the proximity to primary forest. Insectivore activity was best predicted by mist‐netting‐based data, not by point counts. We identified the abundant Indonesian endemic lemon‐bellied white‐eye Zosterops chloris as the main driver of predation on artificial prey. Synthesis and applications. The suppression of arthropods is a major ecosystem service provided by insectivorous birds in agricultural systems world‐wide, potentially reducing herbivore damage on plants and increasing yields. Our results show that avian predation success can be driven by single and abundant insectivorous species, rather than by overall bird species richness. Forest proximity was important for enhancing the density of this key species, but did also promote bird species richness. Hence, our findings are both of economical as well as ecological interest because the conservation of nearby forest remnants will likely benefit human needs and biodiversity conservation alike.